CTNI-15. CLINICAL EFFICACY OF ONC201 IN NEWLY DIAGNOSED DIPG AND IN PREVIOUSLY IRRADIATED PEDIATRIC H3 K27M-MUTANT GLIOMAS. (9th November 2020) - Gardner, Sharon; Koschmann, Carl; Tarapore, Rohinton S; Allen, Jeffrey; Zaky, Wafik; Odia, Yazmin; Hall, Matthew; Daghistani, Doured; Khatib, Ziad; Aguilera, Dolly; MacDonald, Tobey; Fouladi, Maryam; et al.
Abstract: ONC201, an anti-cancer DRD2 antagonist and ClpP agonist, is in Phase II trials for adult H3 K27M-mutant diffuse midline gliomas. In adults, the recommended phase 2 dose (RP2D) of 625mg ONC201 once a week has been established as a biologically active dose that is well tolerated. Radiographic regressions with single agent ONC201 have been reported in adult recurrent H3 K27M-mutant glioma patients. This multi-arm, dose-escalation and dose-expansion trial determined the pediatric RP2D of ONC201 administered as an oral capsule (Arm A) or liquid formulation (Arm E) in post-radiation H3 K27M-mutant glioma (Arm A) or in newly diagnosed DIPG (Arm B) patients. Molecular assessments include intratumoral ONC201 concentrations (Arm C) and CSF H3 K27M DNA levels (Arm D). Enrollment as of April 30, 2020 is complete in Arm A (22) and Arm E (26) and continues in Arm B (18/24), Arm C (5/12), and Arm D (22/24). The RP2D of weekly 625mg ONC201 scaled by body weight was confirmed when administered as a capsule or a liquid formulation as a single agent or in combination with radiation without dose-limiting toxicity. The most frequent adverse events regardless of attribution to the drug were predominantly low grade: ONC201 capsule alone was headache (54.5%), nausea (36.4%), and fatigue (36.4%); ONC201 liquid formulation was vomiting (31.8%), headache (22.7%), VIth nerve disorder (22.7%); ONC201 capsules in combination with radiation (Arm B) was headache (47.1%), vomiting (52.9%), nausea (41.2%). Pharmacokinetic analysis in plasma of Arm A patients revealed T1/2 : 8.4h; Tmax : 2.1h; Cmax : 2.3ug/mL; AUC0-tlast : 16.4ug/mL, with similar exposure across body weights. In conclusion, when scaled by body weight the ONC201 capsule or liquid formulation alone or in combination with radiation were associated with safety and pharmacokinetic profiles in pediatric H3 K27M-mutant diffuse midline glioma patients that are similar to the experience in adults.